Pre-thrombolysis serum sodium concentration is associated with post-thrombolysis symptomatic intracranial hemorrhage in ischemic stroke patients - Wu, Xiaolan; Jiang, Zhuangzhuang; Xu, Dongjuan; Zhang, Rufang; Li, Hongfei (Frontiers in Neurology, 2024)
Background and aim Symptomatic intracranial hemorrhage (sICH) was the most serious complication associated with alteplase intravenous thrombolysis (IVT) in acute ischemic stroke (AIS) patients. However, the relationship between serum sodium levels and post-thrombolysis symptomatic intracranial hemorrhage has not been investigated. Therefore, the aim of this study was to investigate the relationship between pre-thrombolysis serum sodium levels and sICH after IVT, as well as to explore the optimal pre-thrombolysis serum sodium levels for lowering the risk of sICH following IVT. Methods From July 1, 2017 to April 30, 2023, out-of-hospital AIS patients who received IVT in the emergency department were enrolled in this study. Serum sodium levels were measured at admission prior to IVT, and National Institutes of Health Stroke Scale scores were continuously assessed during and after thrombolysis. Routine follow-up neuroimaging was performed between 22 to 36 h after IVT. Initially, three logistic regression models and restricted cubic splines (RCS) were established to investigate the relationship between serum sodium levels and post-thrombolysis sICH. Furthermore, to evaluate the predictive value of serum sodium for post-thrombolysis sICH, we compared area under the receiver operating characteristic curve (AUROC) and net reclassification improvement (NRI) before and after incorporating serum sodium into traditional models. Finally, subgroup analysis was conducted to explore interactions between serum sodium levels and other variables. Results A total of 784 AIS patients who underwent IVT were enrolled, among whom 47 (6.0%) experienced sICH. The median serum sodium concentration for all patients was 139.10 [interquartile ranges (IQR): 137.40–141.00] mmol/L. Patients who developed sICH had lower serum sodium levels than those without sICH [138.20(IQR:136.00–140.20) vs. 139.20(IQR:137.40–141.00), p = 0.031]. Logistic regression analysis (model 3) revealed a 14% reduction in the risk of post-thrombolysis sICH for every 1 mmol/L increase in serum sodium levels after adjusting for confounding variables (p < 0.001). The risk of post-thrombolysis sICH was minimized within the serum sodium range of 139.1–140.9 mmol/L compared to serum sodium concentration below 137.0 mmol/L [odds ratio (OR) = 0.33, 95% confidence interval (CI): 0.13–0.81] in model3. Furthermore, there was a significant trend of decreasing risk for sICH as serum sodium concentrations increased across the four quartiles (P for trend = 0.036). The RCS analysis indicated a statistically significant reduction in the risk of sICH as serum sodium levels increased when the concentration was below 139.1 mmol/L. Incorporating serum sodium into traditional models improved their predictive performance, resulting in higher AUROC and NRI values. Subgroup analysis suggested that early infarct signs (EIS) appeared to moderate the relationship between serum sodium and sICH (p < 0.05). Conclusion Lower serum sodium levels were identified as independent risk factors for post-thrombolysis sICH. Maintaining pre-thrombolysis serum sodium concentrations above 139.1 mmol/L may help reduce the risk of post-thrombolysis sICH.